2021
DOI: 10.1111/imm.13434
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐590‐3p inhibits T helper 17 cells and ameliorates inflammation in lupus mice

Abstract: T helper 17 (Th17) cells have a pathogenic effect in many autoimmune diseases. Inhibition of Th17 cells can alleviate the inflammatory damage in autoimmune diseases. Our previous study found that microRNA‐590‐3p (miR‐590‐3p) was involved in the differentiation of Th17 cells in systemic lupus erythematosus (SLE). Here, we demonstrated that an increase in Th17 cells was correlated with low expression of miR‐590‐3p in patients with SLE and in lupus mice. Upregulation of miR‐590‐3p reduced the differentiation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…An et al reported that the administration of autophagic inhibitor hydroxychloroquine to MRL/lpr mice, which spontaneously develop SLE-like inflammation, ameliorates SLE-induced nephritis pathology, such as mesangial cellular proliferation ( An et al, 2017 ). Consistent with this finding, the administration of an microRNA-590-3p agomir to MRL/lpr mice attenuated the pathology score of lupus nephritis ( Huang et al, 2021 ). In a murine autoimmune myocarditis model, the administration of bazedoxifene reduced Th17 differentiation, resulting in improved myocarditis pathology ( Wang et al, 2021 ).…”
Section: Cd4 + T Differentiationsupporting
confidence: 58%
See 1 more Smart Citation
“…An et al reported that the administration of autophagic inhibitor hydroxychloroquine to MRL/lpr mice, which spontaneously develop SLE-like inflammation, ameliorates SLE-induced nephritis pathology, such as mesangial cellular proliferation ( An et al, 2017 ). Consistent with this finding, the administration of an microRNA-590-3p agomir to MRL/lpr mice attenuated the pathology score of lupus nephritis ( Huang et al, 2021 ). In a murine autoimmune myocarditis model, the administration of bazedoxifene reduced Th17 differentiation, resulting in improved myocarditis pathology ( Wang et al, 2021 ).…”
Section: Cd4 + T Differentiationsupporting
confidence: 58%
“…Similar to Th1 cells, autophagy-deficient Th17 cells are susceptible to cell death. According to Huang et al, autophagy-deficient human CD4 + T cells overexpressing microRNA-590-3p showed reduction of Th17 differentiation by increased apoptosis ( Huang et al, 2021 ).…”
Section: Cd4 + T Differentiationmentioning
confidence: 99%
“…A recent study suggested that miR-590-3p can suppress Th17 cells by inhibiting autophagy; increasing miR-590-3p expression can improve lupus nephritis and skin injury in MRL/lpr mice, providing a possible direction for the treatment of SLE symptoms. 36 The organ most severely damaged by inflammation in SLE is the kidney. MiR-146a reduces kidney injury in MRL/lpr mice by inhibiting the expression of TRAF6 and IRAK1 target genes and contributes to LN treatment.…”
Section: Mirnas and The Diagnosis Of Sle And Lnmentioning
confidence: 99%
“…Lupus erythematosus lesions in the skin share extensive lymphocyte infiltration with a high predominance of CD4 T cells and cytokines, including TNF-α, IL-1α, IL-1β, IL-6, and IL-8 [ 114 ]. Huang et al [ 115 ] found a correlation between the increase in Th17 cells and the decrease in miR-590-3p in systemic lupus erythematosus patients and MRL/lpr mice. miR-590-3p agomir transfection promoted the apoptosis of Th17 cells by autophagy suppression via direct targeting of autophagy-related 7 (Atg7).…”
Section: Mirnas For Treating Inflammatory Skin Diseasesmentioning
confidence: 99%